2020
DOI: 10.1007/s11332-020-00685-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological variables of CrossFit participants: a systematic review

Abstract: Objective This study aimed to review the existing literature concerning the psychological variables of CrossFit participants. Methodology This review followed the PRISMA guidelines and was documented in the PROSPERO registry (CRD42018091177). Six electronic databases (SCOPUS, PubMed, SPORTDiscus, Web of Science, EMBASE, and Cochrane) were searched from their inception through July 2020. The methodological quality of the studies was assessed. Results Thirty-four studies met the inclusion criteria. We observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 58 publications
2
21
0
4
Order By: Relevance
“…Adolescents showed high levels of enjoyment and learning perception after CrossFit practice. Our results are in line with findings by Dominski et al [ 46 , 47 ]. The effects of the CrossFit protocol on fitness level were significant.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Adolescents showed high levels of enjoyment and learning perception after CrossFit practice. Our results are in line with findings by Dominski et al [ 46 , 47 ]. The effects of the CrossFit protocol on fitness level were significant.…”
Section: Discussionsupporting
confidence: 94%
“…In 2020, Alemany-Arrebola et al demonstrated that the worldwide pandemic situation has caused an increase in stress and also showed that a stressful situation (pandemic and confinement) together with a critical event (COVID-19), increases anxiety levels and influences the perception of self-efficacy [ 44 ]. Although the connection between self-esteem and regular physical activity is well documented, Dominski et al (2020) showed a connection between CrossFit training and higher levels of psychological functioning (well-being, affect, body awareness, and self-esteem) [ 45 , 46 ]. Adolescents showed high levels of enjoyment and learning perception after CrossFit practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for staying at cross training indicated that 37.5% of the practitioners aim for more fun activities, 21.9% seek to improve health, and 12.5% practice the modality for social interaction. The data presented corroborate those of previous authors (Tibana et al, 2015;Dominski et al, 2020), which point to a relationship between the challenging character and the motivation for staying and adhering to the modality -with higher levels of social relations, satisfaction, and behavioral regulation. These findings indicate that professionals seek strategies to increase practitioners' adherence and permanence in the cross training modality.…”
Section: Discussionsupporting
confidence: 89%
“…Motivation has been one of the most cited concepts among the reasons that justify athletes' success (Sibley & Bergman, 2018). Besides, it is considered an essential element for the permanence and maintenance in a sports activity, being fundamental in the athlete's conduct, as it awakens and maintains adequate activation levels to regulate the performance-oriented behavior (Dominski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There are activities such as calisthenics, strength/power, weightlifting, gymnastic movements, plyometric exercises, cycling, running, and rowing, which can be performed at a high intensity (Tibana et al, 2019 ). Challenge, scalability, enjoyment, affiliation, and the constant variation of workouts are characteristics that may explain the exponential growth among practitioners of different levels of physical fitness (Dominski et al, 2020 ), including a wide range of populations, including healthy individuals, obese individuals, and athletes. The growth in training with high intensity has aroused the interest of researchers, including our research group, mainly focusing on psychological (Dominski et al, 2020 ) physiological benefits (Tibana et al, 2022 ) as well as injuries (Dominski et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%